The Role of Stakeholders in Guidance for Overcoming Juvenile Delinquency in Cirebon Regency - Safrotulloh, Mohammad; Alauddin, Diaz (Eduprof : Islamic Education Journal, 2025)
Teenagers have a strategic role as the nation's next generation, but their transition period is often marked by various challenges. The physical, psychological and social changes that occur in teenagers encourage them to search for their identity while facing risks such as bullying, brawls, motorbike gangs, drug abuse and other deviant behavior.  The purpose of this study was to understand the relationship between identity styles and risk behaviors in adolescents. Adolescence is often colored by the search for self-identity, which can affect their predisposition to risky behaviors. Understanding these links is important for developing effective interventions in supporting healthy identity formation and preventing risky behaviors in adolescents. This study uses descriptive qualitative methods to understand the phenomenon of juvenile delinquency in Cirebon and the factors that cause it, including aspects of the individual, family, environment, and society. Data were collected through semi-structured interviews with adolescents who had engaged in delinquent behavior, their family members, community leaders, educators, and social workers. In addition, participatory observation is carried out in the environment where the adolescent lives in order to understand the social dynamics that influence their behavior. The analysis of the data was carried out with thematic analysis techniques, identifying patterns and themes that emerged from the data that had been collected. To increase the validity of the findings, data triangulation is used by comparing information from various sources, and member checking by asking informants to review the findings to ensure their accuracy and suitability to their experience. Data shows that cases of juvenile delinquency such as bullying, brawls and motorcycle gangs are often triggered by weak self-control, peer influence and lack of religious and moral guidance. Apart from that, globalization also accelerates access to negative information that influences adolescent behavior. To overcome this problem, various parties have carried out preventive and curative efforts, such as forming special teams, outreach in schools, rehabilitation, mentoring and law enforcement against juvenile delinquents. On the other hand, positive activities involving teenagers need to be increased to develop their potential, both in terms of skills, creativity and moral values. Collaborative efforts between families, schools, communities and government are needed to create an environment that supports the growth of teenagers into individuals who are responsible, independent and contribute to society. With the right guidance and support, teens can overcome their challenges and achieve a better future. The results of this study suggest that adolescents ' identity style plays an important role in their propensity for risky behavior. Adolescents with a diffuse-avoidant identity style, who tend to delay and avoid decision-making, are more prone to behaviors such as aggression, substance use, and delinquency. Conversely, adolescents with an informational and normative identity style, who are proactive in problem solving and adhere to social norms, show a lower tendency towards such behavior. These findings emphasize the need for interventions that encourage the development of healthy identities in adolescents. Educational programs in schools can be designed to encourage self-exploration and commitment to personal values, helping students develop a strong identity. In addition, parents need to be given an understanding of the influence of their level of education and parenting style on adolescent behavior, emphasizing the importance of a supportive and communicative family environment. Community initiatives should also be developed to provide opportunities for youth to engage in positive activities, such as sports or the arts, as safe channels for exploration and identity formation. Mental health support through counseling services that address identity diffusion and equip adolescents with coping strategies to resist peer pressure and avoid maladaptive behaviors is also very important. By adopting these strategies, stakeholders can create an environment that supports the development of a healthy identity, thereby reducing the prevalence of risky behavior among adolescents.